Effect of seedbed steaming on Cylindrocladium floridanum, soil microbes and the development of white pine seedlings - Dumas, M.T.; Greifenhagen, S.; Halicki-Hayden, G.; Meyer, T.R. (Phytoprotection, 1998)
The Egedal® bed steamer produced sufficient heat to kill mierosclerotia of Cylindrocladium floridanum at 5 and 10 cm soil depths in one bareroot forest seedling nursery. At a second nursery, the buried inoculum was killed only to a depth of 5 cm. Soil steaming did not affect the mierosclerotia at 15 cm. The steaming reduced populations of fluorescent pseudomonas to undetectable levels to a depth of 20 cm and populations of Trichoderma species were significantly reduced in the upper 10 cm of the seedbed. Density of white pine seedlings sown in the steamed beds was significantly higher (P= 0.05), and height, root collar diameter, shoot weight and root weight were significantly greater (P= 0.05) 4 months after steaming than that of control seedlings sown in unsteamed beds.